Agronomy in the Lower Kosi Catchment (Nepal) - Bhaskaran, A. R.; Chakravarti, D. C.; Thapa, K. B. (Indian Forester, 1965)
The paper is a short resume of the several observations made by the authors during their tours in the catchment of the Kosi River in Nepal. There is at present no systematic record of the agronomical practices followed in this part of Nepal which is mostly inaccessible by any mode of travel except trekking on foot. It has been emphasized that the agricultural practices of the area need urgent improvement and modernisation. However, the several rational practices noticed in the tract are the result of cumulative experience of the local farmers.